2015
DOI: 10.1002/ange.201505126
|View full text |Cite
|
Sign up to set email alerts
|

Pentafulvene for the Synthesis of Complex Natural Products: Total Syntheses of (±)‐Pallambins A and B

Abstract: The first total syntheses of pallambins Aa nd Ba re enabled by the use of pentafulvene in an unprecedented Diels-Alder reaction. After elaboration of the adduct through chemoselective cyclopropanation, strategic CÀHi nsertion affords the dense tetracyclic core of the natural products.1 ,3-Dipolar cycloaddition and palladium(II)-catalyzed alkoxycarbonylation were leveraged for the construction of the hexacyclic scaffold en route to both natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Indeed, with 4–6 rings, 7–10 contiguous stereocenters, and 2 quaternary stereocenters, these challenging terpenoid isolates are an ideal proving ground for the development of unique strategies and methods. Two elegant approaches to the synthesis of pallambins have appeared, one from the Wong group 2 and the other from the Carreira 3 group. The former route furnished 3 and 4 in 38 steps from the Wieland–Miescher ketone, and the latter afforded 1 and 2 in 23 steps from a fulvene.…”
mentioning
confidence: 99%
“…Indeed, with 4–6 rings, 7–10 contiguous stereocenters, and 2 quaternary stereocenters, these challenging terpenoid isolates are an ideal proving ground for the development of unique strategies and methods. Two elegant approaches to the synthesis of pallambins have appeared, one from the Wong group 2 and the other from the Carreira 3 group. The former route furnished 3 and 4 in 38 steps from the Wieland–Miescher ketone, and the latter afforded 1 and 2 in 23 steps from a fulvene.…”
mentioning
confidence: 99%
“…[244] Pallambins A-D, extracted from the epilithic liverwort Pallavicinia ambigua, [245] show no important biological activity. Wong et al [246] demonstrated the formation of pallambins C (265) and D (266) in 38 steps from the Wieland-Miescher ketone. [247] Baran et al in 2016 reported an 11-step pathway to ( 265) and ( 266), in which 9 of the 11 steps are strategic and masking substituent manipulations are absent.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Pallambins A‐D, extracted from the epilithic liverwort Pallavicinia ambigua , [245] show no important biological activity. Wong et al [246] . demonstrated the formation of pallambins C ( 265 ) and D ( 266 ) in 38 steps from the Wieland‐Miescher ketone [247] .…”
Section: Applications Of Robinson Annulation In the Total Synthesis O...mentioning
confidence: 99%
“…In 2015, Carreiraa nd co-workers creativelyd eveloped aD iels-Alder reactiono fp entafulvene with acrylate to construct the bridged bicyclo[2.2.1] system,w hich represents the first application of pentafulvene-participated cycloaddition reactioni n complex natural product total synthesis. [56] By the use of Trost's two-step protocol [57] involving hydride reduction and Hoffman elimination on stable amine 115,t he highly unstable pentafulvene 116 was prepared and utilized in situ for the desired [4+ +2] cycloaddition with acrylate. Et 2 AlCl was the optimal Lewis acid catalystf or this cycloaddition to smoothly and stereoselectively generate the bridged [2.2.1] cycloadduct 117.…”
Section: Total Synthesis Of Pallambinsaand Bbyr H-catalyzed Càh Insermentioning
confidence: 99%